Observasi Nanofluid dengan TiO2 sebagai Partikel Nano dan Sodium Dodecyl Benzene Sulfonate sebagai Surfaktan untuk Aplikasi Media Quench - Andreas Sugiarto; Aldi Alfarizi; Luthfi Dali Ahmad; Setyoaji Fajar Negara; Ghiska Ramahdita; Sri Harjanto; Wahyuaji Narottama putra (Jurnal Metalurgi dan Material Indonesia, 2019)
Heating and cooling process in heat treatment is a common process to increase the mechanical properties of steel component. Rapid cooling, or quenching, is needed to change the microstructure to obtain the desire hardness. Recently, nanofluid is widely used as a medium for quenching because of their advantage in heat thermal conductivity compared with conventional medium such as water or oil. Nanofluid is a liquid with high thermal conductivity nanoparticle suspended in the fluid base. The variation of nanoparticles content in nanofluids could control the cooling rate to optimize the desired characteristics of a material. TiO2 is widely used as nanoparticle because of its high thermal conductiviy, relatively cheap and environmental friendly. To improve the suspension of TiO2 nanoparticle in nanofluid, surfactant is added. In this research, Commercial grade TiO2 powder was used as nanoparticle, and common household bodycare which contain Sodium Dodecyl Benzene Sulfonate (SDBS) was used as the source of surfactant. The nanofluid was produced by mixing 100 ml water with 0.1% volume TiO2, and additional 1%, 3%, and 5% SDBS surfactant as variation. Before mixing, the TiO2 powder were milled at 500 rpm for 10 hours. This nanofluid was then used as quenching medium. The steel used as sample in this experiment was S45C medium carbon steel, heated at 1000°C for 1 hour. Scanning Electron Microscope (SEM) was used to determine the TiO2 particle size after milling, and showed roughly less than 100 nm. Microstructure observation showed martensite phase formation after quenching. Hardness test confirmed this phase, showing hardness up to 954 HV after quenching using surfactant added nanofluid.